Effects of dietary spent pink guava mesocarp on egg quality of caged and free-range layers - Teoh, Jia Yi (2014)
Pink guava is known to contain high levels of lycopene, a carotenoid that have one of the highest antioxidant activities. Lycopene was also indicated to produce good pigmentation in egg yolk. Feeding studies on laboratory animals using spent pink guava mesocarp (SPGM), which contains lycopene, indicated that SPGM has high antioxidant properties, has lipid–lowering effect and prevented obesity. There is no information regarding the effect of dietary SPGM on other animals such as laying hens. Therefore two studies were conducted to evaluate the SPGM product and its effect on the performance and egg quality of the layer chicken. In the first study, nutrient profiles and lycopene content of three batches of SPGM from different fruit harvesting dates were evaluated and were found to be consistent among batches. The second study was a 9-week feeding trial using a total of 90 ISA Brown layer chicken aged 30 weeks under two management systems. Treatment diets consisted of (i) control diet (without SPGM); (ii) diet with 2.5% SPGM, (iii) diet with 5% SPGM; (iv) diet with 7.5% SPGM, and (v) diet with 10% SPGM. The SPGM used were in dried form. Inclusion of 5% to10% SPGM in layer chicken diet significantly (p<0.05) improved feed intake, Feed Conversion Ratio (FCR), egg production, egg weight, eggshell weight, eggshell thickness, Haugh unit, egg mass, and egg yolk color, regardless of the cage system or free-range system. Yolk color score (based on DSM Yolk Color Fan) improved with SPGM inclusion. The SPGM dietary inclusion from 5% to 10% of SPGM registered yolk color score of up to 6 and 8 for cage rearing and free-ranging, respectively. Lycopene content in egg yolk increased linearly with increased in SPGM inclusion in the diet. Eggs from hens fed with SPGM had a significant lower cholesterol (p<0.05) content compared to the control group. It is concluded that feeding layer hens with SPGM enriched the eggs with lycopene besides improving the yolk color score. These eggs are also lower in cholesterol and SPGM-based eggs can become an alternative health product.